PENGARUH KEBIJAKAN DIVIDEN, DEBT TO EQUITY RATIO, DAN PRICE EARNING RATIO PADA RETURN SAHAM PERUSAHAAN LQ 45 PERIODE 2011-2013 - Nirayanti, Luh Putu Ratih; Widhiyani, Ni Luh Sari (E-Jurnal Akuntansi; Vol 9 No 3 (2014), 2014)
In firms that go public common phenomenon is the fluctuation in the stock return. This study aims to determine the effect of dividend policy (DPR), Debt to Equity Ratio (DER), and Price Earning Ratio (PER) on Stock Return company categorized LQ 45 at the Indonesia Stock Exchange 2011-2013. This study used secondary data obtained at the company in the category LQ 45 at the PT. BEI 2011-2013 with direct access to the idx.co.id. Data analysis was conducted using multiple regression test, and  equipped with Classical Assumption test. The result of the discussion concluded that the dividend policy (DPR), Debt to Equity Ratio (DER), and Price Earning Ratio (PER) has effect simultaneously and  partially to Return Shares of the company are categorized LQ 45 at the Indonesia Stock Exchange 2011-2013.
Keywords: dividend policy, Debt to Equity Ratio, and Price Earning Ratio, and Stock Return